Rosmini’s metaphysical evidence for the existence of God - Swartz, N. P. (Acta Theologica, 2009)
Rosmini is of the opinion that the soul consists of both a bodily (natural) and a godly component. Both components unite in humankind. In Rosmini’s cosmology, humankind is viewed in relation to God and the world (cosmos). Cosmology cannot be comprehensively explained without linking ontology and theology, in particular. Rosmini treats human knowledge of God’s existence ontologically. According to Rosmini, we will not comprehend metaphysical or spiritual matters without understanding temporal matters (cosmology). Cosmology forms part of a higher science, namely ontology and even more so theology. Ontology treats being in its essence, in terms of which Rosmini identifies three forms, namely the ideal, the real (or actual) and the moral. The essence of being in all three forms should be similar, yet these forms differ. Although humankind is equal to the godly image, God and humankind differ in essence. Humankind shares in the ideal, the actual and the moral forms by means of the soul. Rosmini is of the opinion that the moral form, in relation to reality, forms the ideal Being. The ideal Being is infinite and essentially perfect. The infinite perfect Being can therefore not be humankind. Humankind is unable to fully comprehend the perfect Being (God). The perfect Being (God) in his totality and completeness is thus not subject to human knowledge or existence. Human reason can only know what is revealed to it through nature. According to Rosmini, we can know God in a way that surpasses human intelligence, and we can therefore not form a positive but raher a negative understanding of God.